Enhanced energy deposition and carrier generation in silicon induced by two-color intense femtosecond laser pulses - Tani, Mizuki; Sasaki, Kakeru; Shinohara, Yasushi; Ishikawa, Kenichi L (arXiv.org, 2022)
We theoretically investigate the optical energy absorption of crystalline silicon subject to dual-color femtosecond laser pulses, using the time-dependent density functional theory (TDDFT). We employ the modified Becke-Johnson (mBJ) exchange-correlation potential which reproduces the experimental direct bandgap energy \(E_g\). We consider situations where the one color is in the ultraviolet (UV) range above \(E_g\) and the other in the infrared (IR) range below it. The energy deposition is examined as a function of mixing ratio \(η\) of the two colors with the total pulse energy conserved. Energy transfer from the laser pulse to the electronic system in silicon is dramatically enhanced by simultaneous dual-color irradiation and maximized at \(η\sim 0.5\). Increased is the number of generated carriers, not the absorbed energy per carrier. The effect is more efficient for lower IR photon energy, or equivalently, larger vector-potential amplitude. As the underlying mechanism is identified the interplay between intraband electron motion in the {\it valence} band (before excitation) driven by the IR component and resonant valence-to-conduction interband excitation (carrier injection) induced by the UV component. The former increases excitable electrons which pass through the \(k\) points of resonant transitions. The effect of different multiphoton absorption paths or intraband motion of carriers generated in the conduction band play a minor role.